2004
DOI: 10.1097/00004872-200401000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-mediated regulation of the endothelial renin???angiotensin system and vascular cell growth

Abstract: Either low or high levels of insulin suppressed angiotensinogen and renin expression, however, high doses of insulin stimulated ACE activity in cultured human aortic EC. This may indicate that insulin regulates vascular cell growth and endothelial function via bifunctional modification of the vascular angiotensin generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 19 publications
2
29
0
1
Order By: Relevance
“…Ang II mediated production of reactive oxygen species (ROS) promotes growth factors, cytokines and chemotactic factors relating to atherosclerosis [65]. A high level of insulin, as occurs in insulin resistance states, induces the activation of the tissue RAAS in blood vessels and the heart, and leads to an overproduction of Ang II in these tissues [33,58]. High levels of insulin directly activate the expression and production of angiotensin, cell growth through www.intechopen.com the angiotensin I receptor and the conversion of Ang I to Ang II in vascular smooth muscle cells.…”
Section: Stimulated Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…Ang II mediated production of reactive oxygen species (ROS) promotes growth factors, cytokines and chemotactic factors relating to atherosclerosis [65]. A high level of insulin, as occurs in insulin resistance states, induces the activation of the tissue RAAS in blood vessels and the heart, and leads to an overproduction of Ang II in these tissues [33,58]. High levels of insulin directly activate the expression and production of angiotensin, cell growth through www.intechopen.com the angiotensin I receptor and the conversion of Ang I to Ang II in vascular smooth muscle cells.…”
Section: Stimulated Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…High levels of insulin directly activate the expression and production of angiotensin, cell growth through www.intechopen.com the angiotensin I receptor and the conversion of Ang I to Ang II in vascular smooth muscle cells. Although the mechanisms leading to the initial activation of tissue Ang II in high-risk conditions such as type 2 diabetes and hypertension, RAAS blocking agents such as angiotensin converting enzyme inhibitors (ACE inhibitors) and Ang II receptor blockers (ARBs), inhibits the multi-factorial effects of Ang II and reduce the frequency of cardiovascular events as observed in the HOPE and LIFE studies [58,66,67]. The HOPE Study (the Heart Outcomes Prevention Evaluation study) showed that high plasma rennin activity is an independent predictor of major vascular events and mortality in a stable population of high-risk patients with atherosclerosis and/or diabetes [58].…”
Section: Stimulated Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
See 3 more Smart Citations